L’activité antibactérienne des extraits phénoliques et l’huile essentielle d’Urtica dioïca - TALEB, Ali (My University, 2022)
Phytotherapy, offering natural remedies is well accepted by the body. It is currently undergoing an exceptional revival in the West due to the side effects induced by drugs, which worry users who then turn to a gentler medicine. Also, our interest was focused on Urtica dioïca L. is a medicinal plant belonging to the Urticaceae family, this species known as "hourig" is widespread in the Algerian Tell. Plant very used in traditional medicine for its many virtues. The objective of our work was to extract polyphenols from leaves and roots of the nettle, and to evaluate the antimicrobial activity of the different extracts. The antimicrobial activity was determined on ten bacterial strains, according to the agar diffusion method, the disc method and the determination of MICs by the microdilution method on 96-well microplates. All the extracts tested in our study reacted positively on at least one of the tested microbial strains, which confirms that the plant U. dioïca L. is endowed with antimicrobial properties.
Keywords: Urtica dioïca L.; phenolic extract; polyphenols; antimicrobial activity